ChemInform Abstract: [Ru(Bi8)2]6+ — A Cluster in a Highly Disordered Crystal Structure Is the Key to the Understanding of the Coordination Chemistry of Bismuth Polycations. Issue 4 (28th January 2014) - Groh, Matthias F.; Isaeva, Anna; Frey, Christoph; Ruck, Michael
Abstract Black platelets of Bi39.67Ru2Br35.0 are crystallized from a melt of Bi, BiBr3, and Ru (evacuated silica tube, 450 °C, 8 h).